30th Brazilian Society for Virology 2019 Annual Meeting—Cuiabá, Mato Grosso, Brazil - Renata Dezengrini Slhessarenko; Marcelo Adriano Mendes dos Santos; Michele Lunardi; Bruno Moreira Carneiro; Juliana Helena Chavez-Pavoni; Daniel Moura de Aguiar; Ana Claudia Pereira Terças Trettel; Carla Regina Andrighetti; Flávio Guimarães da Fonseca; João Pessoa Araújo Junior; Fabrício Souza Campos; Luciana Barros de Arruda; et al. (Viruses, 2020)
The 30th meeting of the Brazilian Society for Virology (SBV) was held, for the first time in its 30 years of existence, in Cuiabá, the capital of Mato Grosso State, Central Western Brazil, a tropical region between the three richest biomes in the world: Amazon Florest, Cerrado and Pantanal. In recent years, the field of virology has been built in the State. The aim of this report is to support participants and virologists to receive the most up-to-date information about the meeting, which occurred from 16 to 19 October 2019. National and international speakers gave SBV the opportunity to learn about their experience on their virology fields, sharing recent scientific findings, compiling conferences, round table presentations and work presentations in oral and poster sessions. The meeting held over 300 attendants, who were also involved on oral and poster presentations, showing a great variety of recent unpublished studies on environmental, basic, animal, human, plant and invertebrate virology. In addition, SBV offered the Helio Gelli Pereira award for the best research studies in each field presented during the meeting. The 30th meeting of SBV was very productive and has also encouraged scientific partnership and collaboration among virologists worldwide.